A New Perspective on Neutrosophic Differential Equation - R.Sumathi, I.; Mohana Priya, V. (International Journal of Engineering and Technology, 2018)
In this paper the Neutrosophic ordinary differential equation of first order via neutrosophic numbers is epitomized. We also intend to define the neutrosophic numbers and their (Î±, Î², Î³)-cut. Finally a numerical example is given to demonstrate its practicality andÂ Â Â Â Â Â Â Â Â Â Â Â effectiveness of the differential equation involving neutrosophic numbers.Â